Media Innovation Based on Simple Kit for Dynamic Electricity Learning - Subkan Nina (Indonesia Approach Education, 2020)
This study aims to determine the effectiveness of simple KIT-based media in improving student learning achievement in dynamic electricity material. The sample used was the students of class grade 12 of IPA-3 Madrasah Aliyah Negeri 2 Mojokerto, totaling 35 students. The type of research used is research development (Research and Development). The research data were obtained from questionnaire responses during learning and the results of the pre-test and post-test. The questionnaire's responses were as many as 85.14% of students who thought that the development of KIT-based learning media was very effective in using dynamic electricity learning. Moreover, as many as 14.85% think that KIT-based learning media is creative and interactive learning and is an additional supplement in the teaching and learning process. From the test results given to students, there was a significant increase in students' achievements. This indicator can be seen from the t count value is smaller than the t table (t count <t table), then H1 (learning with media treatment) can be applied in learning. Another indicator is that the value of p-value is smaller than alpha 5% (0.05) Ho (learning without treatment) is rejected, so it is concluded that there is a significant increase between learning outcomes before using Simple KIT-based media after implementing learning media using simple KIT